Bioinformatics : analyzing DNA sequence using BLAST - Rahman, Nadim Naimur (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.